Pengaruh Literasi Keuangan dan Belanja Online Terhadap Pengelolaan Keuangan - Fadhilah, Faiz; Animah, Animah (Guna Sewaka, 2025)
This study aims to analyze the influence of financial literacy and online shopping on financial management in household finances. The study used a quantitative approach with a sample of 101 respondents who actively shop online. The sampling technique used was purposive sampling with sample criteria in the form of individuals who are married and active in shopping online. This study contributes by providing guidance for households to improve financial literacy as a basis for managing income and expenses, including in utilizing online shopping platforms wisely. The results of testing and data analysis show that knowledge about finance and online shopping significantly affects financial management in household finances. Suggestions for further researchers are to expand the research sample to various regions with different socio-economic characteristics to obtain a more comprehensive picture. tudies are recommended to take a longitudinal approach to identify long-term trends regarding the influence of financial literacy and online shopping on household financial management